Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Pegawai Bagian Akademik di Politeknik Negeri Medan - Simanjuntak, Siti Maysarah; Prayudi, Ahmad; Parulian, Tohap (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The purpose of this study was to determine the Effect of Work Environment and Work Motivation on the Performance of Academic Section Employees at Medan State Polytechnic. This research is associative research. The population in this study were academic employees at the State Polytechnic of Medan totaling 57 respondents, the calculation of the sample size was carried out using the slovin formula. The data collection methods in this study were observation, interviews and questionnaires. The data analysis method uses descriptive methods and multiple linear regression analysis with a significant level of 0.05. The F-test results show that Work Environment and Work Motivation together have a positive and significant influence on the dependent variable, namely Employee Performance. Based on the test of the coefficient of determination (R2) shows that the Adjusted R Square value of 0.862 means that Work Environment and Work Motivation affect Employee Performance by 86.2% and the remaining 13.8% can be explained by other factors not examined in this study.